The Role of Gut Microbiota in the Prevention or Development of Atherosclerosis – A Review - Marcin Początek; Michał Piotrowski; Piotr Serwicki; Szczepan Pośpiech; Jakub Prosowski (Quality in Sport)
Aim of the study: This study aims to consolidate current knowledge on the role of gut microbiota in atherosclerosis, examining its mechanisms of action, the impact of dietary patterns on microbial composition, and emerging therapeutic interventions.